Pandemic influenza preparedness: The critical role of the syringe - Strauss, Kenneth (Vaccine, 2006)
In the face of an almost unprecedented threat of a global pandemic of influenza it is imperative that stockpiling of appropriate drugs and devices begin now. One vital device is an appropriate syringe for delivering vaccine. With the potential for millions to be infected and the vaccine supply severely stretched it is imperative that the syringe used to vaccinate waste as little vaccine as possible and thus allow for a maximum number of persons to be vaccinated. Our study tested seven leading candidate vaccine syringes for dosing accuracy, dose-capacity per vial, medication wastage and a battery of ergonomic features. One device, the Flu+™ syringe, proved superior to the others in all important categories, possibly due to its low dead-space volume and its dosing accuracy. The data suggest that switching to this device from any of the others tested would provide between 2 and 19% additional vaccine doses per vial if the current 10-dose vials are used. Extrapolations from this data suggest that many thousands to millions of additional persons could be vaccinated in mass campaigns. Use of a syringe of this type, and the vaccine savings that would accrue, would likely be important in reducing morbidity and mortality in the event of a pandemic of influenza.